Skill development and career advancement: survey of the effectiveness of the fiber optic cable professional certification course - CA1C internal network and CA2C external network - Wan Salleh, Wan Mohd Za’im Bin; Mohd Yunus, Mohd Yuaizuddin Bin; Kurasli, Engku Nor Zatun Najhah (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2024)
The employability of graduates requires a holistic student to deal with global competition and technological change. The Ministry of Higher Education through polytechnics has given students the opportunity to obtain various Professional Certifications for student skills. This study focuses on the effectiveness of the Fiber Optic Cable Professional Certification Course. The primary objectives of this study are to evaluate the effectiveness of the course in helping students obtain Fiber Optic Professional Certificate Cable - CA1C Internal Network and CA2C External Network, and to assess the perceived value of the competency certificate for career advancement after graduation. This study was conducted on Diploma in Electronic Engineering (Communication) Students, JKE PKT by using a question instrument survey of 20 students who took this course. Results show more than 85% of students obtained the Professional Certificate of Fiber Optic Cable - Internal Network CA1C and more than 75% obtained External Network CA2C. More than 95% of students have agreed that their level of understanding and knowledge has increased after following this course. The results also found that the majority of students agreed the importance of this Compentency Certificate in their career advancement in the field of study